Observation of interprofessional collaborative practice in primary care teams: An integrative literature review. Issue 7 (July 2015) - Morgan, Sonya; Pullon, Susan; McKinlay, Eileen
Abstract Background Interprofessional collaboration improves patient care, especially for those patients with complex and/or chronic conditions. Many studies examining collaborative practice in primary care settings have been undertaken, yet identification of essential elements of effective interprofessional collaboration in primary care settings remains obscure. Objective To examine the nature of interprofessional collaboration (including interprofessional collaborative practice) and the key influences that lead to successful models of interprofessional practice in primary care teams, as reported in studies using direct observation methods. Design Integrative review using Whittemore and Knafl's (2005) five stage framework: problem identification, literature search, data evaluation, data analysis and presentation. Data sources and review method: Primary research studies meeting the search criteria were accessed from MEDLINE, PsycINFO, Scopus, King's Fund and Informit Health Collection databases, and by hand-searching reference lists. From 2005 to 2013, 105 studies closely examining elements of interprofessional collaboration were identified. Of these, 11 studies were identified which incorporated a range of 'real time' direct observation methods where the collaborative practice of health professionals was closely observed. Results Constant opportunity for effective, frequent, informal shared communication emerged as the overarching theme and most critical factor in achieving and sustaining effective interprofessional collaboration and interprofessional collaborative practice in this review. Multiple channels for repeated (often brief) informal shared communication were necessary for shared knowledge creation, development of shared goals, and shared clinical decision making. Favourable physical space configuration and 'having frequent brief time in common' were key facilitators. Conclusion This review highlights the need to look critically at the body of research purported to investigate interprofessional collaboration in primary care settings and suggests the value of using direct observational methods to elucidate this. Direct observation of collaborative practice in everyday work settings holds promise as a method to better understand and articulate the complex phenomena of interprofessional collaboration, yet only a small number of studies to date have attempted to directly observe such practice. Despite methodological challenges, findings suggest that observation data may contribute in a unique way to the teamwork discourse, by identifying elements of interprofessional collaborative practice that are not so obvious to individuals when asked to self-report.